2022
DOI: 10.3389/fbioe.2022.1076348
|View full text |Cite
|
Sign up to set email alerts
|

A mini-review: Advances in plant-derived extracellular vesicles as nano-delivery systems for tumour therapy

Abstract: Extracellular vesicles are functionally active, nanoscale, membrane-bound vesicles that can be secreted by all cells. They have a key role in most health and disease states and have gradually become a promising class of delivery vehicles for targeted therapies for a variety of diseases. Plant-derived extracellular vesicles have received increasing attention based on their easy availability, non-toxicity and high absorption. However, compared with mammalian extracellular vesicles, the role of these nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…For example, they are unlikely to carry pathogens or cause immune reactions, ensuring higher biosafety; moreover, plant vesicles have specific membrane compositions and structures, enhancing their stability during processing and storage; at the same time, plants can be cultivated on a large scale, making plant-derived vesicles more economical and sustainable; additionally, plant vesicles may be easier to genetically modify and bioengineer, offering greater potential for engineering applications. 51,52 Our preliminary study on P-EVs showed some protection against pancreatic acinar cell injury. Going forward, our research will focus on the composition of P-EVs, aiming to enrich the vesicles with specific bioactive compounds to boost their therapeutic potential and application prospects.…”
Section: T H Imentioning
confidence: 94%
“…For example, they are unlikely to carry pathogens or cause immune reactions, ensuring higher biosafety; moreover, plant vesicles have specific membrane compositions and structures, enhancing their stability during processing and storage; at the same time, plants can be cultivated on a large scale, making plant-derived vesicles more economical and sustainable; additionally, plant vesicles may be easier to genetically modify and bioengineer, offering greater potential for engineering applications. 51,52 Our preliminary study on P-EVs showed some protection against pancreatic acinar cell injury. Going forward, our research will focus on the composition of P-EVs, aiming to enrich the vesicles with specific bioactive compounds to boost their therapeutic potential and application prospects.…”
Section: T H Imentioning
confidence: 94%
“…The lipid membranes of plant-EVs provide robust protection for bioactives against environmental elements, such as alterations in pH, heat, and light, while also demonstrating exceptional stability [ 129 ]. Plant-EVs possess intrinsic active substances from their source plants, endowing them with advantageous biological properties including antioxidant, anti-inflammatory, and anticancer effects [ 130 ]. With their potential to serve as efficient nanodelivery vehicles, plant EVs offer promising prospects for a wide range of cancer treatments.…”
Section: Therapeutic Potential Of Different Sources Of Evs In Cancermentioning
confidence: 99%
“…To address this, Wang and his team effectively reassembled the lipids of grapefruit to form a nanocarrier derived from grapefruit. This approach facilitates the passage of therapeutic medications across the blood–brain barrier and, potentially enhancing the efficacy and stability of drug therapy for brain malignancies [ 130 ]. Plant-EVs, being naturally occurring nanoscale particles, possess the capability to transport molecules including lipids, nucleic acids, and proteins with precision and efficiency in intercellular communication and substance transfer.…”
Section: Therapeutic Potential Of Different Sources Of Evs In Cancermentioning
confidence: 99%
“…Plant-derived EVs have the advantages of low cost, high productivity, and high stability [99]. Plant-derived EVs contain the innate active components secreted by the source plants, which have biological functions such as anti-inflammatory, antioxidant, and antitumor [99]. Therefore, plant-derived EVs can serve as potential drug carriers and therapeutic agents.…”
Section: Plantsmentioning
confidence: 99%